La pile gallo-romaine de Cinq-Mars-la-Pile (Indre-et-Loire) : réexamen du dossier à la lumière des récentes découvertes - Emmanuel Marot (Revue Archéologique du Centre de la France)
The archaeological excavations conducted in 2005 in the Gallo-Roman pillar's surroundings of Cinq-Mars-la-Pile took place before a project to develop the touristic value of this enigmatic pillar, 29,50 m in height, built in bricks on opus caementicium and presenting geometric and polychrome decoration panels on its south face. All the ground on which the pillar stands has been affected by ancient excavations and pillage. However, excavations in the north of the site have revealed a monumental terrase, a semi-excavated building and a statue sculpted in local stone, probably representing a near-eastern prisoner. All of these elements would have functioned at the same time as the pillar, at the end of 2nd century. or the first half of 3rd century AD. After comparisons with similar edifices, it seems now certain that the pillar was erected to indicate the grave of a Turonne elite. The other buildings discovered must have been conceived with the same will of ostentation and could correspond to a mausoleum with a statuary group illustrating a feat of arms to celebrate an honourable ancestor, certainly a soldier of high rank.